Methodism : A Very Short Introduction - Abraham, William J. (William James), 1947- (Great Clarendon Oxford University Press, 2019)
Methodism began as a renewal movement within Anglicanism in the 18th century, dominated the Protestant landscape of the USA in the 19th, and continues to be one ofthe most vibrant forms of Christianity worldwide today. This Very Short Introduction traces Methodism from its origins in the work of John Wesley right up to the present day. Considering the identity, nature, and history of Methodism, William J. Abraham provides a fresh account of its place in the life and thought of the Christian Church.
Include Illustrations and Index
Keywords: Methodism. -- Methodist Church -- Church -- History. -- thought of the Christian Church